Geopolitics of Denial: Turkish State's 'Armenian Problem'. Issue 2 (3rd March 2016) - Aybak, Tunç
Abstract: Denial of the crimes committed against the Armenians during the late Ottoman Empire has been a permanent feature of modern Turkish diplomatic statecraft, which stems from Turkey's geopolitical anxieties closely tied with the nation-building process in the Anatolian lands at the expense of other non-Turkish and non-Muslim minorities. The aim of this article is to examine the current discursive debates and diplomatic statecraft in the construction of the denial policies of the Turkish state. Even though Turkey has now departed from collective amnesia and the Armenian genocide has been opened up to public debate, the denial policy has now become an integral part of the Islamic conservative Justice and Development Party's neo-Ottomanist grand strategy and its regional ambitions. To this extent, the centenary of the Armenian genocide offered an opportunity to the intellectuals and the executers of Turkish statecraft to rebrand its denial policy by deploying diplomatic measures of apology and just memory, and decentring the remembrance that led to the gradual racialization of the Armenian other as a geopolitical threat to the Turkish national identity.